1985
DOI: 10.1002/path.1711470303
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of basement membrane type IV collagen in invasive and metastatic squamous carcinomas of the head and neck

Abstract: The immunohistochemical localization of basement membrane type IV collagen was investigated with a mouse monoclonal antibody in major surgical resections from 25 patients with invasive squamous carcinomas of the head and neck. Irrespective of site, size or stage of the disease, the 16 primary invasive tumours were almost completely surrounded by a layer of type IV collagen. Focal abnormalities were regularly present, consisting of thickening and aggregation of type IV collagen together with attenuation and seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Mechanisms involved in basement membrane loss in the carcinomatous tissue remain unclear. It has been suggested that this loss is due to a lack or to a decrease of synthesis, decreased assembly, and increased turnover or degradation of basement membrane components by the tumor cells Daneker et al, 1987;Carter et al, 1985). The results of the present study revealed that such an event may occur not only in FIGURE 4 -Absence of basement membrane in the areas showing dense stromal inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 54%
“…Mechanisms involved in basement membrane loss in the carcinomatous tissue remain unclear. It has been suggested that this loss is due to a lack or to a decrease of synthesis, decreased assembly, and increased turnover or degradation of basement membrane components by the tumor cells Daneker et al, 1987;Carter et al, 1985). The results of the present study revealed that such an event may occur not only in FIGURE 4 -Absence of basement membrane in the areas showing dense stromal inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 54%
“…These co-localizations were not observed in normal mucosa. In OSCC, the formation of a basement membrane, especially in welldifferentiated carcinomas, has been known for a long time (Carter et al 1985). Haas et al (2001) reported an increased expression of Ln-5 in hyperplastic oral mucosa as compared to normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that BM is comprised of various components, including collagens, laminin, fibronectin etc. Among them, type IV collagen acts as the basic skeleton with all of the other components attaching onto it [8][9][10]. Recently, there have been several studies about the distribution pattern of BM in different organs but the conclusions are controversial.…”
Section: Introductionmentioning
confidence: 99%